PRAKTIK KEWARGANEGARAAN EKOLOGIS MELALUI PROGRAM ECO GREEN DI SMAN 1 KUSAN HILIR - Hamidah, Rizka; Hiliadi, Wardiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The main issue in this research is the low level of environmental care practices among students in the school environment. Ecological citizenship practices as a form of citizen responsibility towards the environment need to be instilled from an early age. The Eco Green program is one of the school's efforts to foster ecological citizenship practices among students. This study aims to determine and analyze ecological citizenship practices through the Eco Green Program at SMAN 1 Kusan Hilir. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing stages. The results showed that: (1) The implementation of the Eco Green Program is carried out through school environment cleaning activities, waste sorting, and making eco bricks as a form of environmentally friendly waste management. (2) Ecological citizenship practices are reflected in the active involvement of students, habituation of environmentally caring behavior, and the application of responsibility values towards the environment in school life.